Brudstykker af en Dagbog, holdt paa en Reise i Danmark. (Fortsat fra side 215) - Ramert, D. J. (Tidsskrift for Landøkonomi, 2018)
Brudstykker af en Dagbog, holdt paa en Reise i Danmark. (Fortsat fra side 215)